Maqashid Sharia, Business Ethics and Sharia Economic Transactions (A Review of the Hadith of the Prophet Muhammad) - Eva Andriani; Muhammad Asad Mubarok Al Jauhari; Syovinatus Sholicha; Arifatul Ma'ani (International Journal of Economics (IJEC), 2023)
Business ethics in activities in the field of sharia economic transactions is the spearhead of realizing an ideal muamalah system, especially making maqashid syari'ah the main guide in business activities. The estuary in each transaction is the main assessment in the principle of the transaction, because if at the end of the transaction there is a right that is overridden then it becomes a problematic transaction. The existence of maqashid syari'ah as a principle in business ethics and muamalah transactions has implications for maintaining the rights of each party involved in a transaction, so that in the end it ends in mutual consent ('antaradlin), in religious values ​​such a transaction is a transaction good things and have an impact on their safety in this world and the hereafter, because religion directs all activities to succeed in this world and the hereafter.